Efficacy and safety of Wenxin Keli combined with metoprolol tartrate in the treatment of premature ventricular contractions: A systematic review and meta-analysis - Huang, Ping; Luo, Yining; Chen, Jiaxue; Xu, Jingke; Shi, Yuanshu; Chen, Guoren; Ma, Ping (Frontiers in Cardiovascular Medicine, 2022)
Background Wenxin Keli (WXKL) has good clinical value in the treatment of premature ventricular contractions, but there is insufficient evidence to support it. This study evaluates the efficacy and safety of WXKL combined with metoprolol tartrate in the treatment of ventricular premature beats (VPCs). Methods We searched seven databases to identify randomized controlled trials (RCTs) for this study. Two reviewers independently screened and extracted the data. The Cochrane Manual criteria were used for methodological quality assessment. Meta-analyses were performed using Review Manager 5.4.1 software. Risk ratios (RR) were used for effect sizes for dichotomous data, demonstrated in effect sizes and 95% confidence intervals (CIs). Results A total of 11 RCTs of WXKL combined with metoprolol tartrate in the treatment of premature ventricular contractions were included in this study. Meta-analysis showed that WXKL combined with metoprolol tartrate (treatment group) was more effective than metoprolol tartrate (control group) in improving premature ventricular contractions (RR = 1.32, 95% CI: [1.24, 1.40], P < 0.00001); significantly improved the rate of premature ventricular contractions (RR = 1.32, 95% CI: [1.23, 1.41], P < 0.00001); there was no difference in adverse drug reactions compared with the control group (RR = 0.61, 95% CI: [0.35, 0.1.05], P = 0.08), but the number of adverse reactions (n = 18) was less than that of the control group (n = 32), and the severity was lower than that of the control group. The included studies only mentioned randomization and did not describe the generation of random sequences in detail. Conclusion This study found that Wenxin Keli combined with metoprolol tartrate in the treatment of premature ventricular contractions increased the efficacy of the drug, reduced the occurrence of adverse reactions, and reduced the severity of adverse reactions. Due to the quality limitations of the included studies, more high-quality RCTs are needed in the future to provide more evidence for longer-term analyses.